2012
DOI: 10.1002/ajmg.a.35653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fat distribution in Prader–Willi syndrome: Relationships with adipocytokines and influence of growth hormone treatment

Abstract: Marked anthropometric changes are seen in Prader-Willi syndrome (PWS). Emaciation is observed during infancy, whereas severe obesity is found in older children and adults. Growth hormone (GH) treatment modifies the anthropometric changes in PWS patients. In this study, we examined changes in the body composition of 51 PWS patients (age range, 6-54 years; median, 16.5 years), with a focus on the amount of abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT), VAT/SAT ratio, and serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
4
27
0
1
Order By: Relevance
“…It could also be explained by an altered adipocyte function during GH treatment. Wölfing et al [44] showed that GH treatment stimulates secretion of adiponectin in cultured adipocytes, and a Japanese study observed a negative relation between the amount of visceral adipose tissue and adiponectin levels in patients with PWS [45]. However, clinical studies in girls with Turner syndrome and in short children born small for gestational age showed no significant relation between GH treatment and adiponectin [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…It could also be explained by an altered adipocyte function during GH treatment. Wölfing et al [44] showed that GH treatment stimulates secretion of adiponectin in cultured adipocytes, and a Japanese study observed a negative relation between the amount of visceral adipose tissue and adiponectin levels in patients with PWS [45]. However, clinical studies in girls with Turner syndrome and in short children born small for gestational age showed no significant relation between GH treatment and adiponectin [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In adult GH deficiency, continued GH treatment has already been reported to maintain body composition, improve lipid abnormalities, and reduce the risk of CVD 36) . Considering PWS, Tanaka et al 37) reported that during GH treatment, although scAT increased, VAT remained low. However, after indications for GH in PWS were no longer met and GH treatment had been discontinued, the degree of obesity was similar to that of the group never treated with GH.…”
Section: Role Of Growth Hormonementioning
confidence: 99%
“…The adiposity was low among adult PWS patients while continuing growth hormone therapy, but it increased with age to similar levels to untreated patients once growth hormone was ceased (Tanaka, Abe et al 2013). In obese subgroup of adult PWS patients, adiponectin, which is cardio-protective (Bluher and Mantzoros 2015), was low as visceral adiposity increased, and was negatively correlated with total cholesterol, low-density lipoprotein and triglyceride (Tanaka, Abe et al 2013). During childhood the metabolic phenotype in PWS is more favourable compared to obese controls (Haqq, Muehlbauer et al , Brambilla, Crino et al 2011).…”
Section: 13: Measuring Eementioning
confidence: 88%
“…In an adult PWS study, both visceral and subcutaneous adipose tissue increased with increasing age (Tanaka, Abe et al 2013). The adiposity was low among adult PWS patients while continuing growth hormone therapy, but it increased with age to similar levels to untreated patients once growth hormone was ceased (Tanaka, Abe et al 2013). In obese subgroup of adult PWS patients, adiponectin, which is cardio-protective (Bluher and Mantzoros 2015), was low as visceral adiposity increased, and was negatively correlated with total cholesterol, low-density lipoprotein and triglyceride (Tanaka, Abe et al 2013).…”
Section: 13: Measuring Eementioning
confidence: 96%
See 1 more Smart Citation